2015
DOI: 10.1039/c5nr05354d
|View full text |Cite
|
Sign up to set email alerts
|

Effects of crystallographic facet-specific peptide adsorption along single ZnO nanorods on the characteristic fluorescence intensification on nanorod ends (FINE) phenomenon

Abstract: The precise effect of crystallographically discriminating biomolecular adsorption on the fluorescence intensification profiles of individual zinc oxide nanorod (ZnO NR) platforms was elucidated in this study by employing peptide binding epitopes biased towards particular ZnO crystal surfaces and isolating the peptides on given crystalline facets of ZnO NRs. Subsequently, the fluorescence emission profiles of the preferentially bound peptide cases on the basal versus prismic planes of ZnO NRs were carefully eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…The fluorescence panel in Figure 2(A) with all polarizations allowed during excitation and collection clearly shows the characteristic FINE phenomenon we have previously reported. 10,11,15,28,43 The unique behavior of FINE originates from the coupled and waveguided emission from the fluorophores placed on top of the ZnO NR which travels through the NR via the mechanisms of subwavelength waveguiding and surface evanescent wave propagation. 10,11,28 This optical signal is highly intensified and spatially localized at the NR termini, as clearly displayed in the fluorescence intensity graph plotted as a function of the position along the long axis of the NR in the right panel of Figure 2(A).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The fluorescence panel in Figure 2(A) with all polarizations allowed during excitation and collection clearly shows the characteristic FINE phenomenon we have previously reported. 10,11,15,28,43 The unique behavior of FINE originates from the coupled and waveguided emission from the fluorophores placed on top of the ZnO NR which travels through the NR via the mechanisms of subwavelength waveguiding and surface evanescent wave propagation. 10,11,28 This optical signal is highly intensified and spatially localized at the NR termini, as clearly displayed in the fluorescence intensity graph plotted as a function of the position along the long axis of the NR in the right panel of Figure 2(A).…”
Section: Resultsmentioning
confidence: 99%
“…10,11,14,28 When examining the temporal and spatial characteristics of enhanced biomolecular fluorescence on individual ZnO NRs, we found that both the signal intensity and photostability along the NR length show strikingly different profiles relative to those on conventional polymeric platforms. 10,11,29 Unlike the spatially uniform signal observed on polymers, both the magnitude and temporal stability of the fluorescence signal from fluorophore-coupled biomolecules on ZnO NRs were not only much increased relative to those on polymers but also highly intensified at the NR ends relative to the NR main body.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…We have previously demonstrated that ZnO NRs can be successfully employed in bioanalyte detection [ 12 , 13 , 14 , 29 , 30 , 31 , 32 , 33 ]. In these efforts, pristine ZnO NRs served as efficient subwavelength waveguides and surface evanescent wave carriers, which subsequently permitted ultrasensitive detection of DNA- and protein-derived fluorescence signals.…”
Section: Introductionmentioning
confidence: 99%